Forest Honey Cream Formulation and Test of Its Effectiveness in Accelerating Burn Wound Healing - Sugiyanto; Aprianti Sigala; Putri Clara (Jurnal Penelitian Pendidikan IPA, 2025)
Honey contains various essential nutrients, including carbohydrates, proteins, amino acids, vitamins, minerals, dextrin, plant pigments, and natural compounds. This study aims to develop the formulation and effectiveness of forest honey cream as a therapeutic agent for second-degree burns. The research design used was a pure experimental laboratory. This study used five rabbits divided into five treatment groups. Burns were given on the first day and treatment was given every day. Observations were made every three days for 15 days. Statistical analysis was carried out using a Completely Randomized Design (CRD), and the Least Significant Difference (LSD) test, by comparing the condition of the wound before and after treatment, as well as the control group that was not given treatment. The results of the study showed that based on the test of the effectiveness of healing burns between the 30% concentration honey cream group when compared to the positive control group (Biopacenton® ointment) showed a difference but was not very significant (0.03 < 0.07). The calculated F value is greater than the F table at the level of α = 0.05 (8.70 > 2.78) so the hypothesis Ho is rejected and Ha is accepted which means that there is a significant influence/effect of administering high concentration forest honey cream formulation on burns in rabbit test animals. In conclusion, the application of forest honey at a higher concentration significantly improves burn healing in the rabbit model. Further research is recommended to investigate the optimal frequency of forest honey application to further accelerate the burn healing process.